The use of internet applications for the dissemination of knowledge for career management - Lloyd, Brenda (Curtin University, 2012)
This research investigates the interaction between Internet based communication, knowledge management in a virtual environment and career management in the Internet environment. The aim was to combine the students’ need for good career information with the technology used in multiplayer interactive 3D gaming environments, which the Internet generation find so engaging, supplemented by artificial intelligent “bots”.The literature indicates that while the professionals within career management are apprehensive about the effect the use of the Internet and technologies will have on their position within the workforce, they are in fact, adapting by refocusing and redefining their roles. The tools which are available are varied, meaning that some at least could prove useful in this area. The research already completed in the fields of both career management and the development of the tools was examined.In order to explore how these tools and the Internet are currently used, a cross section of employers was interviewed. A questionnaire was developed and distributed to a group of 128 students from different subject majors within a polytechnic. These were also followed by short interviews where the student had indicated a willingness to do this. In all cases, the use of the newer technologies such as 3D worlds and simulations was discussed to assess the openness of the participants on both sides to their use.The data from the questionnaires were coded and SPSS was used to analyse all but the open-ended questions. The open-ended questions and the qualitative data from the interviews were analysed with the help of NVivo.The more adventurous students would use the newer technologies, but almost all of them said they would use the Internet to look for, and possibly, apply for positions. The employers all used the Internet to advertise positions, with most of them using such tools as video conferencing for interviews. There was a mix of opinions in the area of whether they would still need to meet the person before employing them. The general feeling regarding the newer technologies was that if they reached a point where they were easy to access and use, and made the job of recruitment easier, they would use them.The fact that the younger generation use the Internet and the applications currently available not only for entertainment and work, but for all aspects of their lives including socialising, means that the use of similar tools and technologies would attract more interest and involvement from this group.Globalisation means that all aspects of our lives are becoming intertwined with differing countries and cultures and career management is no exception. The pool of potential positions is greater, as is the pool of potential employees. This means that any development which makes the matching of the two has to be good. This research explored the perceptions and openness of all roles within this area to the use of the technologies. The development of tools which are not acceptable or useful to all parties is a waste of time and money.This research has shown that there are no perceived barriers which cannot be overcome, and while the developments in these areas are likely to progress at a pace which could be uncomfortable for some, the participants in this research can see no reason why the Internet and its surrounding technologies cannot be very useful in the processes involved with ensuring suitable career options.